Biomarkers for the assessment of chlorpyrifos effects on earthworms and on soil functional parameters - Piola, Lucas; Fuchs, Julio; Oneto, María Luisa; Basack, Silvana; Giménez, Rosana; Massaro, Rubén; Papa, Juan Carlos; Kesten, Eva; Casabé, Norma (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effects of chlorpyrifos on earthworms and on soil functional parameters. An integrated laboratory-field study was performed in a wheat field in Argentina, sprayed with chlorpyrifos at two recommended application rates (240 or 960 g ha-1 a.i.). Laboratory tests included neutral red retention time, comet assay (single cell gel electrophoresis), and avoidance behavior, each using the earthworm Eisenia andrei exposed in soil collected 1 or 14 days after pesticide application, and the bait-lamina test. Field tests assessed organic matter breakdown using the litterbag and bait-lamina assays. Earthworm populations in the field were assessed using formalin application and hand-sorting. The neutral red retention time and comet assays were sensitive biomarkers to the effects of chlorpyrifos on the earthworm E. andrei; however, the earthworm avoidance test was not sufficiently robust to assess these effects. Feeding activity of soil biota, assessed by the bait lamina test, was significantly inhibited by chlorpyrifos after 97 days, but recovered by the 118th day of the test. Litterbag test showed no significant differences in comparison to controls. Earthworm abundance in the field was too low to adequately test the sensitivity of this assessment endpoint.